A multicenter validation of the revised version of the Milan system for reporting salivary gland cytology (MSRSGC). (October 2020) - Mazzola, F.; Tomasoni, M.; Mocellin, D.; Dalè, M.; Iandelli, A.; Carobbio, A.; Marchi, F.; Filauro, M.; Petruzzi, G.; Massa, B.; Facchetti, M.; Battocchio, S.; et al.
Highlights: FNA cytology can obtain a precise insight of the salivary gland lumps. The MSRSGC is a 6-tiered classification which estimates the risk of malignancy (ROM). The revised MSRSGC supplements FNA cytology with some crucial clinical consideration. Abstract: Introduction: Fine-needle aspiration cytology (FNAC) is a basic step in the diagnosis of salivary gland tumors that have a wide variety of histological types. The recent Milan system for reporting salivary gland cytopathology (MSRSGC) can correlate the risk of malignancy with precise cytological features. A revised version was recently proposed to improve the surgical relevance and facilitate uniform management. Material and methods: A multicenter study retrospectively used the original and revised MSRSGC criteria to classify a series of patients who received surgery after FNAC. Results: We enrolled 503 patients from three tertiary centers. The risk of malignancy for the MSRSGC resulted 19.5% in cat. I, 14.3% in cat. II, 17.6% in cat. III, 3.6% in cat. IVa, 24.6% in cat. IVb, 66.7% in cat. V, and 96.8% in cat. VI. The results from the revised MSRSGC were consistent with the original values. Conclusion: The MSRSGC is a promising classification system. In our opinion, the revised version of the MSRSGC supplements FNAC with some crucial clinical information and can better identify the appropriate treatment in each category.